Virtual Reality Enhances Gait in Cerebral Palsy: A Training Dose-Response Meta-Analysis - Ghai, Shashank; Ghai, Ishan (Frontiers in Neurology, 2019)
Virtual-reality training can influence gait recovery in children with cerebral palsy and acquired brain injury. However, a consensus concerning its influence on spatiotemporal gait parameters, and specific training dosage is still needed. This study aims to analyse the influence of virtual-reality training (relevant training dosage) on gait recovery in children with cerebral palsy and acquired brain injury. A search was performed by two reviewers according to PRISMA guidelines on nine databases: PEDro, EBSCO, MEDLINE, Cochrane, Web of science, EMBASE, ICI, Scopus, and PROQUEST. Of 989 records, 14 studies involving a total of 396 children with cerebral palsy and acquired brain injury met our inclusion criteria. 81% of the studies reported significant enhancements in gait performance after training with virtual reality. Meta-analyses revealed positive effects of virtual-reality training on gait velocity (Hedge’s g: 0.76), stride length (0.76), cadence (0.80) and Gross motor function measure (0.45). Sub-group analysis reported a training duration of 20-30 minutes session for ≤4 times per week across ≥8 weeks to allow maximum enhancements in gait velocity. This study provides evidence for the beneficial influence of virtual-reality training in gait rehabilitation for children with cerebral palsy and acquired brain injury.